Building gender equity in the academy : institutional strategies for change - Laursen, Sandra; Austin, Ann E. (Johns Hopkins University Press, 2020)
Despite decades of effort by federal science funders to increase the numbers of women holding advanced degrees and faculty jobs in science and engineering, they are persistently underrepresented in academic STEM disciplines, especially in positions of seniority, leadership, and prestige. Women filled 47% of all US jobs in 2015, but held only 24% of STEM jobs. Barriers to women are built into academic workplaces: biased selection and promotion systems, inadequate structures to support those with family and personal responsibilities, and old-boy networks that can exclude even very successful women from advancing into top leadership roles. But this situation can--and must--change. In Building Gender Equity in the Academy, Sandra Laursen and Ann E. Austin offer a concrete, data-driven approach to creating institutions that foster gender equity. Focusing on STEM fields, where gender equity is most lacking, Laursen and Austin begin by outlining the need for a systemic approach to gender equity. Looking at the successful work being done by specific colleges and universities around the country, they analyze twelve strategies these institutions have used to create more inclusive working environments, including • implementing inclusive recruitment and hiring practices, • addressing biased evaluation methods, • establishing equitable tenure and promotion processes, • strengthening accountability structures, particularly among senior leadership, • improving unwelcoming department climates and cultures, • supporting dual-career couples, • offering flexible work arrangements that accommodate personal lives, • promoting faculty professional development and advancement ; Laursen and Austin also discuss how to bring these strategies together to create systemic change initiatives appropriate for specific institutional contexts. Drawing on three illustrative case studies--at Case Western Reserve University, the University of Texas at El Paso, and the University of Wisconsin-Madison--they explain how real institutions can strategically combine several equity-driven approaches, thereby leveraging their individual strengths to make change efforts comprehensive. Grounded in scholarship but written for busy institutional leaders, Building Gender Equity in the Academy is a handbook of actionable strategies for faculty and administrators working to improve the inclusion and visibility of women and others who are marginalized in the sciences and in academe more broadly